2018
DOI: 10.1161/jaha.117.007868
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Ambulatory Blood Pressure as Predictors of Diastolic Left Ventricular Function in a Flemish Population

Abstract: BackgroundNo longitudinal study compared associations of echocardiographic indexes of diastolic left ventricular function studies with conventional (CBP) and daytime ambulatory (ABP) blood pressure in the general population.Methods and ResultsIn 780 Flemish (mean age, 50.2 years; 51.7% women), we measured left atrial volume index (LAVI), peak velocities of the transmitral blood flow (E) and mitral annular movement (e′) in early diastole and E/e′ 9.6 years (median) after CBP and ABP. In adjusted models includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, a cross-sectional study included 376 hypertensive patients showed that most of the parameters of the LV diastolic function (including E/e') were significantly deteriorated in the reverse dippers, with nocturnal systolic BP fall independently associated with LV diastolic function 42 . Moreover, ABPM appears superior to conventional BP in association with 9.5-years later E/e′ in longitudinal study 43 . However, only one longitudinal (over 20 years of follow up) study including 414 middle-aged subjects from OPERA cohort, 24-hour mean, daytime mean and nighttime mean pulse pressure, but neither different circadian BP profiles, showed significant association with the development of LV diastolic dysfunction as determined by E/e' >=15, even after adjustment with significant baseline clinical characteristics 44 .…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, a cross-sectional study included 376 hypertensive patients showed that most of the parameters of the LV diastolic function (including E/e') were significantly deteriorated in the reverse dippers, with nocturnal systolic BP fall independently associated with LV diastolic function 42 . Moreover, ABPM appears superior to conventional BP in association with 9.5-years later E/e′ in longitudinal study 43 . However, only one longitudinal (over 20 years of follow up) study including 414 middle-aged subjects from OPERA cohort, 24-hour mean, daytime mean and nighttime mean pulse pressure, but neither different circadian BP profiles, showed significant association with the development of LV diastolic dysfunction as determined by E/e' >=15, even after adjustment with significant baseline clinical characteristics 44 .…”
Section: Discussionmentioning
confidence: 78%
“…35 Moreover, ABPM appears superior to conventional BP in association with 9.5 years later E/e′ in the longitudinal study. 36 However, only 1 longitudinal (over 20 years of follow-up) study including 414 middle-aged subjects from the Oulu Project Elucidating Risk of Atherosclerosis cohort (OPERA), 24-hour mean, and daytime mean and nighttime mean pulse pressure, but neither different circadian BP profiles, showed significant association with the development of LV diastolic dysfunction as determined by E/e′≥15, even after adjustment with significant baseline clinical characteristics. 37 Moreover, patients with diabetes were reported to have higher nocturnal BP and higher morning BP surge 10 ; however, it was unknown whether nocturnal hypertension contributes to the progression of LV diastolic dysfunction in patients with diabetes with pre-HF phase.…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, ABPM appears superior to conventional BP in association with 9.5 years later E/eʹ in the longitudinal study. 36 However, only 1 longitudinal (over 20 years of follow-up) study including 414 middle-aged subjects from the Oulu Project Elucidating Risk of Atherosclerosis cohort (OPERA), 24-hour mean, and daytime mean and nighttime mean pulse pressure, but neither different circadian BP profiles, showed significant association with the development of LV diastolic dysfunction The covariates in each multiple linear regression analysis model included age, male gender, BMI, smoking history, the presence of hypertension and dyslipidemia, HbA1c and baseline E/eʹ, time point (y), the patterns of nocturnal hypertension, and the interaction term between time point (y) and the patterns of nocturnal hypertension. BMI indicates body mass index; HbA1c, hemoglobin A1c; and SBP, systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired LV relaxation and elevated left atrial pressure are common findings in patients with hypertension and may ultimately lead to the syndrome of heart failure [26]. Evidence of early diastolic LV dysfunction can be detected in patients with high BP even before the development of LV hypertrophy [27], and masked hypertension may predict the future development of diastolic LV dysfunction [28]. We assessed characteristics of LV filling by pulsed wave and tissue Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 99%